2019
DOI: 10.5004/dwt.2019.24223
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of porous iron – zirconium mixed oxide fabricated ethylene diamine composite for removal of cationic dye

Abstract: Synthesis of iron-zirconium binary oxide fabricated ethylene diamine (IZBO-en) composite involved two step synthesis including mixed binary oxide synthesis followed by synthesis of binary oxide-ethylene diamine composite. Mixed binary oxide was synthesized by co-precipitation method using ammonia as neutralizing agent. Binary oxide based ethylene diamine composite was synthesized using sodium dodecyl sulfate and potassium persulfate as reagents in reaction. Yield of product was 88%. Characterization of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 54 publications
2
3
0
Order By: Relevance
“…The data table is given in the Supporting Information (Tables S3 and S4). Similar observations were reported earlier. …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The data table is given in the Supporting Information (Tables S3 and S4). Similar observations were reported earlier. …”
Section: Resultssupporting
confidence: 92%
“…In line with this, we have earlier shown that bimetallic oxides, metal oxide-fabricated ethylene diamine composites, refined pyrolusite, cobalt oxide nanoparticles, and nickel oxide nanoparticles work well with various dyes. …”
Section: Introductionsupporting
confidence: 63%
“…We have previously shown the synthesis of binary iron-zirconium-mixed metal oxide using the coprecipitation technique and related composites for the removal of dyes. 50 , 51 , 58 Recently, we have shown sucrose-supported self-sustained combustive synthesis of nanoscale cobalt oxide and its dye detoxification property. 59 Major processes that were followed to synthesize nickel oxide-based adsorbents are precipitation, sol–gel, hydrothermal, and microwave heating.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown the synthesis of binary iron-zirconium-mixed metal oxide using the coprecipitation technique and related composites for the removal of dyes. ,, Recently, we have shown sucrose-supported self-sustained combustive synthesis of nanoscale cobalt oxide and its dye detoxification property . Major processes that were followed to synthesize nickel oxide-based adsorbents are precipitation, sol–gel, hydrothermal, and microwave heating. Herein, we report the upscale synthesis of nickel oxide nanoparticles (NONPs) by sucrose-supported, self-propagating combustion of nickel nitrate hexahydrate and its high efficiency for malachite green (MG) removal in the batch process.…”
Section: Introductionmentioning
confidence: 99%
“…We have earlier reported co-precipitation-induced synthesis of binary iron–zirconium-mixed metal oxide and ethylene diamine composites derived thereof for excellent removal of various dyes. , Herein, we report synthesis of cobalt oxide nanoparticles (CONP) by sucrose-assisted, self-sustained combustion of cobalt nitrate, and its remarkable efficiency for malachite green (MG) removal in a systematic batch mode.…”
Section: Introductionmentioning
confidence: 99%